2022
DOI: 10.3390/diagnostics12061319
|View full text |Cite
|
Sign up to set email alerts
|

Schwannoma of the Upper Limb: Retrospective Study of a Rare Tumor with Uncommon Locations

Abstract: Background: Although schwannoma (neurilemmoma) is the most common tumor of the peripheral nerve, its low incidence, slow growth and vague symptoms often lead to misdiagnosis or delayed diagnosis. The aim of the study is to present a series with a large number of schwannomas in the upper limbs, some with very rare occurrence. Methods: We report 17 patients with a mean age of 58.5 years and upper limb schwannomas, located on the median, ulnar and radial nerves, but also on the posterior interosseous nerve and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…There is no gender preference and this lesion was reported within the age range of 30–60 years old. In our case, the patient is a 52-year-old man which is supported by the evidence of mean age reported by Pertea et al [7] (58.5 years), Majumder et al [11] (48 years), and Hirai et al [12] (56 years). This finding suggested that the older age group might have a higher risk of schwannoma occurrence.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…There is no gender preference and this lesion was reported within the age range of 30–60 years old. In our case, the patient is a 52-year-old man which is supported by the evidence of mean age reported by Pertea et al [7] (58.5 years), Majumder et al [11] (48 years), and Hirai et al [12] (56 years). This finding suggested that the older age group might have a higher risk of schwannoma occurrence.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the presence of major neurological signs such as pain, paresthesia, and tingling sensation suggests an unfavorable post-operative outcome. In our patient, despite the history of recurrence and a long onset of growth, there were no neurological problems and the Tinel sign was negative [1] , [7] . Thus, a good prognosis can be expected.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations